Serving Us Rights: Securing the Right to Food in Canada - Tung, Audrey Gemma; Cloutier, Denise; Rose-Redwood, Reuben (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2021)
In recent decades, Canada has consistently failed to uphold basic human rights, including the right to food. This has caused widespread and persistent household food insecurity (HFI) which has become a serious, albeit overlooked, public health concern. Working from a political economic perspective, this article situates HFI within the context of the poverty resulting from neoliberal “rollbacks” to the welfare state. The majority of community and policy responses to HFI focus on the production or redistribution of food, which misses the underlying issue of inadequate income. These responses may even perpetuate food insecurity by offloading safety net functions onto corporations and communities that cannot compensate for welfare programs. In order to strengthen income-based responses to food insecurity, we recommend policy interventions under the “right to food” framework, which places primary responsibility on the state. But unlike traditionally legal conceptions of the right to food, we emphasize its utility as a tool for mobilizing civil society, which is a powerful yet underutilized source of accountability to state obligations. This approach therefore combines political action with policymaking, and civil society with senior governments, in the collective realization of the right to food.